1997
DOI: 10.1007/s11664-997-0191-8
|View full text |Cite
|
Sign up to set email alerts
|

Surface cleaning and etching of CdZnTe and CdTe in H2/Ar, CH4/H2/Ar, and CH4/H2/N2/Ar electron cyclotron resonance plasmas

Abstract: This paper compares H2/Ar, CH4/H2/Ar and CH4/H2/N2/Ar plasma etch processes for CdZnTe and CdTe substrates in view of their potential to provide high-quality substrate surfaces for subsequent HgCdTe epitaxy. An electron cyclotron resonance source was used as plasma generator, and ellipsometry, angle-resolved x-ray photoelectron spectroscopy and low energy electron diffraction were applied to characterize roughness, composition, and order of the resulting substrate surfaces. It was found that CdZnTe is much mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] However, ICP plasma processing, used in HgCdTe, is still maturing and continued research is needed. 4,7,14 ICP plasma processing may also be used to replace conventional wet chemical clean-up, and even be used in the surface preparation for epitaxy of II-VI materials.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] However, ICP plasma processing, used in HgCdTe, is still maturing and continued research is needed. 4,7,14 ICP plasma processing may also be used to replace conventional wet chemical clean-up, and even be used in the surface preparation for epitaxy of II-VI materials.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Several studies have also reported the effect that high-density ''dry'' electron cyclotron resonance (ECR) plasmas have on HgCdTe epitaxial properties. [5][6][7][8][9][10][11][12][13][14] However, ICP plasma processing, for use in HgCdTe, is still maturing and continued research is needed. 4,7,14,15 ICP plasma processing may also be used to replace conventional wet chemical clean-up, and can even be used in the surface preparation for epitaxy of II-VI materials.…”
Section: Introductionmentioning
confidence: 99%
“…With the use of etchants, material is often etched irregularly, and the surface becomes contaminated with reaction products and etchant components. All kinds of final washing solve this problem only partially [1][2][3]. Therefore, the search for optimal methods of surface treatment is continued.…”
Section: Introductionmentioning
confidence: 99%